Ordinance No. 1: Protecting Public Morality, Order and Safety, undated, reprinted in Ordinances of the Town of Bedford 4 (1869) - (:unkn) unknown (My University, 1869)
§ 16: Prohibited discharging any gun, pistol, other firearms, on or across any street, sidewalk, or alley within the corporate limits of the town. Violators fined not exceeding three dollars.
Keywords: DISCHARGE